Relationship between nursing care during hospitalization and the patient's coping ability after surgery for cancer - Conti, Avelina V.
This study was undertaken to determine the relationship between nursing care during hospitalization and the patient's ability to cope with the handicap after surgery for cancer of the colon and/or rectum. "When needs of patients with cancer of the colon and/or rectum are met during the hospitalization period, will this help patient cope better with his handicap?" - was the guide question in the study. The design of the study was experimental, using the method of difference where the extraneous variables were controlled as much as possible while the independent variable was manipulated. The independent variable was applied to the experimental subjects but withheld from the contro subjects. The writer identified and assessed the needs of the ...